2021
DOI: 10.1155/2021/9930777
|View full text |Cite
|
Sign up to set email alerts
|

Antiskin Cancer and Antioxidant Activities of Formulated Agar from Brown Seaweed Laminaria digitata (Hudson) in Dimethyl Benzanthracene-Induced Swiss Albino Mice

Abstract: This study explores the antiskin cancer effect of formulated agar (FA) from Laminaria digitata on dimethyl benzanthracene- (DMBA-) induced skin cancer mice. The agar was extracted and formulated (emulgel), and FA was biochemically characterized. The in vitro cytotoxicity of FA was tested using NTT 3T3 mice fibroblast cells. The mice were divided into 5 groups: group 1 served as control mice, group 2 mice were considered as DMBA-induced cancer control, group 3 mice were FA pretreated (low dose) + DMBA-induced m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…In this aspect, protein exhibited host-pathogen interactions and immunomodulatory potential, whereas lipids including long-chain fatty acids and short-chain fatty acids improve the healthy metabolism in cardiovascular and obesity-related diseases [6]. In addition, vitamins can also trigger the metabolic pathways in human health [2,12,[29][30][31][32]47]. Due to the properties of proteins, lipids, and vitamins, laminarin possesses immunostimulatory activity.…”
Section: Immunomodulatorymentioning
confidence: 99%
See 1 more Smart Citation
“…In this aspect, protein exhibited host-pathogen interactions and immunomodulatory potential, whereas lipids including long-chain fatty acids and short-chain fatty acids improve the healthy metabolism in cardiovascular and obesity-related diseases [6]. In addition, vitamins can also trigger the metabolic pathways in human health [2,12,[29][30][31][32]47]. Due to the properties of proteins, lipids, and vitamins, laminarin possesses immunostimulatory activity.…”
Section: Immunomodulatorymentioning
confidence: 99%
“…George et al [29] reported on the role of beta-1, 3-glucan derived from brown algae, which they showed had antitumor potential in hepatocellular carcinoma, colon cancer, leukemia, and melanoma. Their conclusions were also supported by Bae et al [14].…”
Section: Cancermentioning
confidence: 99%
“…[12][13][14] Using the new drugs for cancer treatments has significantly reduced morbidity and mortality by regulating some key cell receptors and immune responses. [15,16] The rhizome extract and powder of Atractylodes lancea (Thunb) DC is used in traditional Chinese, Thai, and Japanese medicine to treat various illnesses and health problems, including gastrointestinal pain, rheumatoid arthritis, fever, and cold. [17,18] However, the main chemical identified from A. lancea is atractylodin.…”
Section: Introductionmentioning
confidence: 99%